Brawler : stories [large type] - Groff, Lauren (Random House Large Print, 2026)
"Ranging from the 1950s to the present day and moving across age,class, and region-from New England to Florida to California-these nine stories reflect and expand upon a shared theme: the ceaseless battle between humans' dark and light angels" --Provided by publisher.